PEMANASAN GLOBAL, EKSPLOITASI SUMBERDAYA PERIKANAN, DAN PENCEMARAN PESISIR SEBAGAI PENYEBAB UTAMA PERUBAHAN EKOLOGI LAUT DI INDONESIA - Hadiyanto Hadiyanto (Pusat Penelitian Oseanografi LIPI, 2019)
GLOBAL WARMING, OVERFISHING, AND COASTAL POLLUTION AS MAJOR CAUSES OF MARINE ECOLOGICAL CHANGES IN INDONESIA. Changes in marine ecology are normal, because the earth is dynamic, and are getting worse and faster since human are involved in their processes, indicating the Anthropocene Era begins. Consequently, three parameters to measure the quality of the earth for living, i.e. climate changes, rate of biodiversity loss, and nitrogen cycles, have been over the maximum thresholds. In general, changes in marine ecology are caused by phenomena that are occuring in global scale (e.g. increasing of CO emission, global warming, and ocean acidification), regional scale (e.g. overfishing, and changes in oceagraphical processes, rain and storm), and local scale (e.g. eutrophication, sedimentation, pollution, biological invasions, herbivory, and diseases). Result of reviews shows that major causes of changes in marine ecology in Indonesia may be global warming, overfishing, and coastal pollution. As a result, species richness, abundance, distribution, and community structure of marine ecosystems in Indonesia change significantly.